RESILIENSI PADA WANITA YANG MENGALAMI ABORTUS SPONTANEA - Imanika Bunga Ayu (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstrack The purpose of this research is to provide a depiction of the resilience of women who had experienced spontaneous abortion. The research method used is descriptive quantitative. The authors use questionnaires based on the dimensions of resilience resilience by Reivich & Shatte (2002). Characteristics of the survey respondents were women who had experienced a spontaneous abortion, aged 18-40 years, and had never married. Respondents totaling 44 people were taken by purposive sampling technique. Results showed resilience try out the scale reliability scores are interpreted 0.813 resilience questionnaire is reliable. The test data is done with SPSS version 16.00. The results of this research, indicate that the level of resilience of women who had experienced a spontaneous abortion was 27 respondents are in a high level of resilience, 17 respondents were in medium level of resilience. Keyword : Resilience, Women, Spontaneous Abortion